DYSTOCIA IN GOAT DUE TO TRIPLETS: A CASE REPORT - Gaikwad, Sandeep; Choudhari, Ravindra; Gulavane , Sarita (The Indian Journal of Animal Reproduction, 2024)
Dystocia means difficult birth. Does particularly carrying twins or triplets show a higher incidence of dystocia. It is a major cause in goats leading to loss of kids and /or dams, hence economic losses to the farmers. The foetal factors which include oversized foetus, kid malpresentation, malposition, postural defects, and congenital abnormalities(Jackson, 1995). The maternal factors which include over feeding of dam during pregnancy, uterine inertia in polytocous doe, and small diameter of pelvic canal. Dystocia inflicted trauma and infection decreases future fertility (Aziz and Taha, 1996). However the successful treatment of the dystocia depends upon correct diagnosis of the cause and technique used to relieve it.